Idiopathic Hepatic Granulomatosis: A Challenging Case of Fever of Unknown Origin - Ashutosh Garg; Vivek Pal Singh; Jai Khullar; Afreen Khan (Indian Journal of Medical Specialities)
For any physician, fever of unknown origin (FUO) is an enigmatic problem, while being equally frustrating. It tests the limits of patience of both the physician and the patient. While the majority of such cases end up being of infective etiology, the rest are attributable to noninfectious inflammatory disorders (NIIDs) and neoplasms. Among the NIIDs, most turn out to be connective tissue disorders (CTDs). CTDs are commonly known to have granulomas on histopathology. However, hepatic granulomas are rarely encountered. We present a case of FUO in an elderly urban North Indian businessman who after thorough workup was diagnosed with idiopathic hepatic granulomatous disease. Response to disease-modifying therapy was rewarding.